Influencing mechanisms of solid-phase asphaltene precipitation in crude oil of Yongjin Oil Field, Junggar Basin - Yang YANG; Dongxiao ZHANG; Hao WANG; Zengmin LUN; Zhiwei GAO; Rui WANG; Wei HU (Shiyou shiyan dizhi)
Solid-phase asphaltene precipitation and deposition, commonly occurring during reservoir development, lead to reservoir damage and production well blockage, seriously affecting crude oil exploitation and reducing economic efficiency. Solid-phase asphaltene precipitation is affected by the properties of crude oil and temperature/pressure condition, and is a thermodynamic issue involving complex gas-liquid-solid three-phase behavior. This study aims to investigate the solid-state precipitation pattern and its influencing mechanisms of asphaltenes in crude oil from the Yongjin Oil Field, aiming to provide theoretical support for the rational prevention of asphaltene deposition during reservoir development. High-asphaltene-content crude oil from the Yongjin Oil Field was selected as the research object. Crude oil composition analysis, pressure-volume-temperature (PVT) high-pressure physical property analysis, gas injection, and solid-phase asphaltene precipitation experiments were conducted to reveal the precipitation pattern of asphaltenes under different conditions. Based on the cubic plus association (CPA) equation of state (EoS), a three-phase equilibrium calculation model for the oil-gas-asphaltene system was established. The model was fitted to experimental results and used to further simulate the precipitation pattern of asphaltenes under complex conditions, clarifying the effects and their influencing mechanisms of fluid composition, temperature, pressure, and production well operation strategies on solid-phase asphaltene precipitation. The results showed that fluid composition and temperature/pressure conditions were the intrinsic factors and external conditions, respectively, influencing asphaltene precipitation in the system, and the like-dissolves-like principle could fully explain the mechanism of complex phase behavior changes in asphaltenes. After gas injection, the fluid composition was altered, and its influence on crude oil and asphaltene phase behavior was primarily determined by the miscibility of injected gas with crude oil and the extraction and stripping of intermediate components. Production well operation strategies affected asphaltene precipitation by controlling temperature and pressure variations during crude oil flow, thereby determining the location of precipitation. Risk assessment of asphaltene deposition and blockage requires comprehensive analysis integrating reservoir conditions, wellbore structure, and production dynamics.